The ciliary transition zone protein TMEM218 synergistically interacts with the NPHP module and its reduced dosage leads to a wide range of syndromic ciliopathies. Issue 14 (6th February 2022) - Epting, Daniel; Decker, Eva; Ott, Elisabeth; Eisenberger, Tobias; Bader, Ingrid; Bachmann, Nadine; Bergmann, Carsten
Abstract: Mutations in genes that lead to dysfunctional cilia can cause a broad spectrum of human disease phenotypes referred to as ciliopathies. Many ciliopathy-associated proteins are localized to the evolutionary conserved ciliary transition zone (TZ) subdomain. We identified biallelic missense and nonsense mutations in the gene encoding the transmembrane protein TMEM218 in unrelated patients with features related to Bardet–Biedl, Joubert and Meckel–Gruber syndrome (MKS) and characterized TMEM218 as a major component of the ciliary TZ module. Co-immunoprecipitation assays resulted in the physical interaction of TMEM218 with the MKS module member TMEM67/Meckelin that was significantly reduced by the TMEM218 missense change harboured by one of our patients. We could further validate its pathogenicity by functional in vivo analysis in zebrafish ( Danio rerio ) as a well-established vertebrate model for ciliopathies. Notably, ciliopathy-related phenotypes were most prominent by genetic interactions with the NPHP module component Nphp4. Conclusively, we describe TMEM218 as a new disease gene for patients with a wide spectrum of syndromic ciliopathy phenotypes and provide evidence for a synergistic interaction of TMEM218 and the NPHP module crucial for proper ciliary function.